The Effectiveness of Human Resources Performance from the Indonesian National Police Organization in Maintaining Regional Security and Public Order in Indonesia - Jean Silvana Bolang; Mirwan Surya Perdhana (Quantitative Economics and Management Studies, 2023)
Performance is the contribution level made by employees to the goals of their work units and companies/organizations as a result of their behavior and the implementation of their skills, abilities, and knowledge (Bacal, 2015: 153). The performance of Indonesian National Police (Polri) members is essential in an effort to achieve the goals that have been set following the police vision and mission. Polri makes performance a strategic instrument to measure the ability of its members to carry out their duties based on the laws that have been regulated. This study aims to analyze and describe the effectiveness of the human resources performance of the National Police Organization in maintaining regional security and public order in Indonesia. The results revealed that the improvement of Human Resources performance that the National Police Organization has carried out had not provided optimal results until now. This can be seen from the survey, which states a lower level of public trust in the National Police than in other law enforcement agencies, which is only 66.3%. More of this is due to the high number of disciplinary violations of police members from the 2018-2021 period reaching 8,760 violations. Thus, it impacts the poor image of the police in the community as well as the effectiveness of the performance of organizational human resources in maintaining regional security and community order that needs to be optimally implemented. It is evidenced by the number of crimes that occur in the community is still 34,894 cases in 2021 to all provinces in Indonesia nowadays.